Factors affecting the political mobilization of the Lambunao sulod-bukidnons in relation to their ancestral land claim. - Betita, Ma. Antonette Rose Suela
The respondents of the study are the Sulod-Bukidnons (Bukidnons) of Jayobo, Lambunao, Iloilo. Their land had been included under the reservation area of the West Visayas STate University - College of Agriculture and Forestry (WVSU-CAF) by virtue of Presidential Proclamation No. 429. Thus, their aim is to regain the land that belonged to them. The study sought to determine the following objectives: (1) the basis of land claims by the Bukidnons, (2) the forms of political mobilization conducted over their land claims (3) the factors that affect it, and (4) the role of the outside sectors in asserting their land claims ., The study was descriptive and exploratory in nature which employed structured interview to gather data from 91 Bukidnon respondents age 18 years old and above. Key Informant Interviews with the President and Vice-President of Bukidnon United Tribe Association (BUTA) and direct observation were also used. Chi-square (with 0.05 level of significance) was used as a statistical tool to determine the relationship of the variables. The results of the study showed that ancestral domain/inheritance was the basis of the Bukidnons in claiming their lands. The Bukidnons have utilized three forms of conventional and non-violent political mobilization: negotiations,petitions and assemblies. Age is one factor that affected Bukidnons to participate in negotiations. The study showed that Bukidnons above 60 did not participate in the negotiation. Higher educational attainment is also a factor that engaged them in negotiation. The lack of awareness of the size of the land involved in the conflict made the Bukidnons not participative. Also, the minimal importance given by the Bukidnons to their land in terms of housing and self-determination made them not participate in the negotiation. In the filing of petitions as another form of mobilization, only the awareness on the negotiation of Certificate of Ancestral Domain Title (CADT) was seen as a factor for the Bukidnons to engage in such mobilization. The reason for this was that they saw the filing of petitions as a way to ahsten up the granting of Ancestral Domain Title (ADT). Assembly was another mobilization where most members had participated. Membership in BUTA was seen as a factor in joining the assembly. Attendance in assemblies showed sense of membership and support to the cause of their association. The presence of help from outside sectors and the help from both members and leaders of BUTA likewise encouraged Bukidnons to be participative in assemblies. PANLIPI Legal Assistance Center, National Commission on Indigenous Peoples and Philippine Association for Intercultural Development played a major role in helping the cause of the Bukidnons. They had provided legal and technical assistance to the IPs. Lastly, the awareness on the petition filed and their assertion over their land claims made the Bukidnons to mobilize. The findings showed that the Bukidnons have been long working for the granting of their ancestral domain title. They perceived that once their ADT has been granted to them, the issue with WVSU will also be resolved. They do not oppose the presence of the university in the barangay; most of them simply ask to redefine the land and regain the area that belonged to them. At the end of the study, the researchers recommend further academic studies on the political mobilization of the Bukidnons. A policy recommendation is advised that BUTA members should take active role on the issue. Inforamtion dissemination and inculcation of IPs' rights can be decisive factors to increase participation in mobilization. NCIP should give uttermost importance to the granting of the land of IPs and be more responsive to the needs and grievances of the IPs.